The Use of Clustering and Paraphrasing to Teach Reading for General Communication - Astried Damayanti Astried; Sri Utami Dewi; Wawan Prasetyo (STKIP PGRI Trenggalek, 2023)
The research was conducted in Reading for General Communication Class for first semester students of English Education Study Program of STKIP PGRI Trenggalek. The purpose of the research was to implement clustering and paraphrasing to help students comprehend the passage of descriptive paragraph. To get the data, the researchers used observation checklist, test and questionnaire. The test was formed in paraphrasing of passage given. The questionnaire was delivered to get information about the students’ responses during the use of clustering in learning reading. Based on the students’ work, it shows that their reading comprehension was good after the use of clustering. The average of their paraphrasing was 82.34. The questionnaire’ result also indicates that the students gave positive and good response during the use of clustering. It assisted them to get the idea of the paragraph and expressed in their paraphrase.